Native Speakerism and Employment Discrimination in English Language Teaching - Albert Maganaka (Canadian Society for Studies in Education, 2023)
The terms 'native speaker' and 'non-native speaker' are commonly used in English Language Teaching (ELT). Such terminologies create segregation and negatively affect the morale of some non-native English-speaking teachers (NNEST). Using the lens of Critical Race Theory, this paper investigates native speakerism (NS) through a review of literature, specifically on hiring practices or employment discrimination in ELT. It intends to contribute to the dismantling of such native and non-native speaker dichotomy and to establish a more impartial and equitable ELT profession. The terminologies in this literature review were selected through a keyword selection; namely, "native speakerism," "employment discrimination," and "hiring practices." Google Scholar and the online library of a large research university were employed to search for publications in a comprehensive list of databases, including JSTOR, English Teaching & Learning, and ERIC. Using thematic content analysis, articles were categorized into the following themes: Native Speaker Preference, Hiring Criteria, Salary, Advertisements, and Microaggressions. The analysis of 14 relevant articles shows that employment discrimination still prevails in the ELT profession. As studies on employment discrimination in the Canadian ELT industry are lacking, there is a dire need to conduct further research in this area and context.